2020
DOI: 10.1007/s11757-020-00583-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistent juvenile offenders as a special challenge in prison and social-therapeutic treatment

Abstract: Zusammenfassung Von den Strafverfolgungsbehörden werden Jugendliche und Heranwachsende als Intensivtäter (IT) registriert, die in der Vergangenheit nicht nur wiederholt, sondern auch mit schweren Gewaltdelikten strafrechtlich in Erscheinung getreten sind und bei denen die Gefahr einer sich verfestigenden kriminellen Karriere besteht. Der vorliegende Beitrag befasst sich mit der Erreichbarkeit junger IT durch die kriminalpräventiven Maßnahmen des Jugendstrafvollzuges. In einer Vollerhebung der sozialtherapeutis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(8 reference statements)
0
1
1
Order By: Relevance
“…This result is contrary to our expectations, considering that the investigated social-therapeutic unit includes essential features that have been shown to be effective in juvenile offender treatment [e.g., cognitive-behavioral interventions with highrisk offenders (10)(11)(12)]. Further, it is not consistent with the results of a preliminary study, which found a treatment effect on non-violent recidivism (28). Therefore, some aspects that may have affected the results should be considered here.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…This result is contrary to our expectations, considering that the investigated social-therapeutic unit includes essential features that have been shown to be effective in juvenile offender treatment [e.g., cognitive-behavioral interventions with highrisk offenders (10)(11)(12)]. Further, it is not consistent with the results of a preliminary study, which found a treatment effect on non-violent recidivism (28). Therefore, some aspects that may have affected the results should be considered here.…”
Section: Discussioncontrasting
confidence: 91%
“…Guéridon and Suhling (27) point out that these studies provide heterogeneous results and have some methodological weaknesses (e.g., lack of control group). In a preliminary study, social-therapeutic treatment had a positive effect on nonviolent recidivism but not on violent recidivism among police-supervised serious offenders (28).…”
Section: Social Therapy In Germanymentioning
confidence: 87%